PROSPECTS FOR DEWEYAN DEMOCRACY IN BRAZIL: THE OBSTACLES TO DEVELOPMENT IN THE SOCIO-POLITICAL DIMENSIONPERSPECTIVAS DA DEMOCRACIA DE DEWEY NO BRASIL: OS OBSTÁCULOS AO DESENVOLVIMENTO NA DIMENSÃO SOCIO-POLÍTICA - Rego, George Browne; Kellogg, Frederic (Duc In Altum - Cadernos de Direito, 2020)
The purpose of the present work is to discuss how democracy on Dewey's perspective could contribute to the development of countries like Brazil. In order to question this, we need first to understand the background discussion of development in the Latin American context. Therefore, we will present the course and main ideas about the development of the so-called “Dependency Theories” in the Latin American continent.